Intratesticular testosterone is increased in men with Klinefelter syndrome and may not be released into the bloodstream owing to altered testicular vascularization – a preliminary report. (12th February 2014) - Tüttelmann, F.; Damm, O. S.; Luetjens, C. M.; Baldi, M.; Zitzmann, M.; Kliesch, S.; Nieschlag, E.; Gromoll, J.; Wistuba, J.; Simoni, M.
Summary Klinefelter syndrome (KS, 47, XXY) is associated with low serum testosterone (T), long thought to arise from disturbed steroidogenesis in Leydig cells. However, intratesticular testosterone (ITT) concentrations were recently found to be normal in a KS mouse model (41, XXY*). So far, nothing was known about ITT concentrations in human patients with KS. Therefore, ITT, sex hormone‐binding globulin (SHBG) and histological parameters were measured in human testicular biopsies of 11 KS patients, 30 azoospermic patients with Sertoli‐cell‐only syndrome and nine men with normal spermatogenesis as controls. ITT concentrations showed an overall pronounced excess over intratesticular SHBG in molar terms and were significantly increased in men with KS despite of reduced serum T levels. While the ratio of ITT/serum T was markedly increased in KS, the ITT/LH‐ratio was comparable between all groups. After finding significantly increased ITT levels in men with KS, a finding even more striking than in the 41, XXY* KS mouse model, we set out to find a possible 'vascular' explanation for the lack of T release into the testicular blood stream. In testis biopsies from patients, reliable analysis of the vessels is, however, not possible because of the bias resulting from the dissection technique requiring avoidance of larger blood vessels to prevent bleeding. Consequently, the blood vessel constitution was evaluated in whole testis sections from adult male 41, XXY* and 40, XY* mice (n = 5, each). Indeed, the blood vessel/testes surface ratio correcting for the smaller testes of XXY* mice was significantly lower in these mice compared with XY* controls. In conclusion, testicular T production does not seem to be impaired in men with KS. On the contrary, ITT concentrations are increased, but not because of increased SHBG activity. The data from the mouse model let us speculate that a reduced vascular bed might be involved in lower release of T into the bloodstream.